2019
DOI: 10.3389/fgene.2019.01237
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Novel, Sensitive, and Specific Urine-Based Test for Recurrence Surveillance of Patients With Non-Muscle-Invasive Bladder Cancer in a Comprehensive Multicenter Study

Abstract: Bladder cancer (BC), the most frequent malignancy of the urinary system, is ranked the sixth most prevalent cancer worldwide. Of all newly diagnosed patients with BC, 70-75% will present disease confined to the mucosa or submucosa, the non-muscle-invasive BC (NMIBC) subtype. Of those, approximately 70% will recur after transurethral resection (TUR). Due to high rate of recurrence, patients are submitted to an intensive follow-up program maintained throughout many years, or even throughout life, resulting in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 81 publications
2
70
0
Order By: Relevance
“…In a multicentric validation study, Uromonitor presented a sensitivity of 73.5% in the detection of TURB confirmed recurrence, with a specificity of 73.2% and overall good performance across stage and grade [56]. The values were comparable and similar to gold standard cystoscopy performance that presented values of 79.4% and 73.2% for sensitivity and specificity, respectively.…”
Section: Uromonitor and Uromonitor-v2mentioning
confidence: 61%
See 2 more Smart Citations
“…In a multicentric validation study, Uromonitor presented a sensitivity of 73.5% in the detection of TURB confirmed recurrence, with a specificity of 73.2% and overall good performance across stage and grade [56]. The values were comparable and similar to gold standard cystoscopy performance that presented values of 79.4% and 73.2% for sensitivity and specificity, respectively.…”
Section: Uromonitor and Uromonitor-v2mentioning
confidence: 61%
“…Uromonitor-V2 added Kirsten rat sarcoma viral oncogene homolog (KRAS) hotspot detection to the Uromonitor kit. The Uromonitor-V2 test presented in a multicenter study achieved 100% sensitivity, 83.3% specificity, a Positive Predictive Value (PPV) of 66.7% and a Negative Predictive Value (NPV) of 100% among 122 NMIBC patients undergoing "conventional" surveillance for NMIBC [56].…”
Section: Uromonitor and Uromonitor-v2mentioning
confidence: 99%
See 1 more Smart Citation
“…Since these alterations present, at this time, some of the most common genetic events in NMIBC tumors, it became imperative to elucidate their potential to detect NMIBC recurrence in urine. In a previous multicenter study on NMIBC patients, in follow-up the test showed promising results with a sensitivity, specificity, and NPV of respectively 100%, 83.8%, and 100% in a subgroup of 24 NMIBC recurrent patients [ 26 ]. With this current study, we aimed to validate these results in an independent cohort of NMIBC patients in follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Most molecular tests are very expensive and difficult to analyze, but even in that field of diagnostics, there have been attempts to produce commercially available tests with high sensitivity and specificity at lower costs than in previous years. Mutations of TERT and FGFR3 can easily be detected by Uromonitor, a urinary based fast test that showed high sensitivities and specificities in an actual study [14].…”
mentioning
confidence: 99%